2020
DOI: 10.1111/jors.12499
|View full text |Cite
|
Sign up to set email alerts
|

Are the most productive regions necessarily the most successful? Local effects of productivity growth on employment and earnings

Abstract: Economists typically celebrate productivity growth as the chief way to improve living standards. They also advocate that particular cities and regions strive to be as productive as possible to attract business and increase employment. However, while productivity growth may reduce costs, improve quality, or lead to innovation and new products, if demand is insufficiently elastic, labor demand may decrease, reducing employment in that location. In other words, places experiencing the most productivity growth may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
(105 reference statements)
0
6
0
Order By: Relevance
“…Listing the other results, Partridge et al (2021) shown on the negative link between productivity growth and employment growth. On the sample of industries, he has found a weak negative link between productivity growth and employment growth in the case of the computer industry, however, most of the other employmentproductivity results were insignificant.…”
Section: Discussionmentioning
confidence: 89%
“…Listing the other results, Partridge et al (2021) shown on the negative link between productivity growth and employment growth. On the sample of industries, he has found a weak negative link between productivity growth and employment growth in the case of the computer industry, however, most of the other employmentproductivity results were insignificant.…”
Section: Discussionmentioning
confidence: 89%
“…As a consequence, differences in product market conditions and industry composition across countries can explain differences in labor market performance of these countries. To illustrate this, we introduce a simple macro model following Appelbaum and Schettkat (2001) (see also Möller, 2001; Partridge et al, 2021), which is similar to Bessen's (2019) and is based on three equations: πjgoodbreak=QjLj,$$ {\pi}_j=\frac{Q_j}{L_j}, $$ Pjgoodbreak=zjWjπj,$$ {P}_j=\frac{z_j{W}_j}{\pi_j}, $$ Qjgoodbreak=f()Pj,y,with0.25emQjfalse/Pj<0,0.5emQjfalse/y>0,$$ {Q}_j=f\left({P}_j,y\right),\mathrm{with}\ \partial {Q}_j/\partial {P}_j<0,\kern0.5em \partial {Q}_j/\partial y>0, $$ where πj$$ {\pi}_j $$ is labor productivity (in industry j ) given by production quantity Qj$$ {Q}_j $$ divided by the level of employment Lj$$ {L}_j $$. Equation () is a price‐setting function based on a mark‐up calculation.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
“…Calculating growth rates and rearranging the equations lead to expressions using elasticities (the price elasticity εj=PjQj0.25emQj0.25emPj$$ {\varepsilon}_j=\frac{P_j}{Q_j}\frac{\partial\ {Q}_j}{\partial\ {P}_j} $$ and =yQQjy$$ =\frac{y}{Q}\frac{\partial {Q}_j}{\partial y} $$, the income elasticity). Inserting dynamic versions of Equations () and () into Equation () leads to (see especially Partridge et al, 2021): Ltrue^jgoodbreak=ηjtruey^goodbreak−()εjgoodbreak+1πtrue^jgoodbreak+εjWtrue^j.$$ {\hat{L}}_j={\eta}_j\cdot \hat{y}-\left({\varepsilon}_j+1\right)\cdot {\hat{\pi}}_j+{\varepsilon}_j\cdot {\hat{W}}_j. $$ …”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations